Big cats at large: Density, structure, and spatio‐temporal patterns of a leopard population free of anthropogenic mortality. Issue 3 (27th February 2019) - Balme, Guy; Rogan, Matt; Thomas, Lisa; Pitman, Ross; Mann, Gareth; Whittington‐Jones, Gareth; Midlane, Neil; Broodryk, Mark; Broodryk, Kerryn; Campbell, Michelle; Alkema, Marc; Wright, Dave; et al.
Abstract: Human impact is near pervasive across the planet and studies of wildlife populations free of anthropogenic mortality are increasingly scarce. This is particularly true for large carnivores that often compete with and, in turn, are killed by humans. Accordingly, the densities at which carnivore populations occur naturally, and their role in shaping and/or being shaped by natural processes, are frequently unknown. We undertook a camera‐trap survey in the Sabi Sand Game Reserve (SSGR), South Africa, to examine the density, structure and spatio‐temporal patterns of a leopard Panthera pardus population largely unaffected by anthropogenic mortality. Estimated population density based on spatial capture–recapture models was 11.8 ± 2.6 leopards/100 km 2 . This is likely close to the upper density limit attainable by leopards, and can be attributed to high levels of protection (particularly, an absence of detrimental edge effects) and optimal habitat (in terms of prey availability and cover for hunting) within the SSGR. Although our spatio‐temporal analyses indicated that leopard space use was modulated primarily by "bottom‐up" forces, the population appeared to be self‐regulating and at a threshold that is unlikely to change, irrespective of increases in prey abundance. Our study provides unique insight into a naturally‐functioning carnivore population at its ecological carrying capacity. Such insight can potentially be used to assess the health of other leopard populations, inform conservation targets, and anticipate the outcomes of population recovery attempts. Abstract : Human impact across the globe is near pervasive and studies of carnivore populations free of anthropogenic mortality are increasingly scarce. We provide rare insight into the spatio‐temporal patterns, structure and density of a leopard population largely unaffected by people. Such insight can potentially be used to assess the health of other leopard populations, inform conservation targets, and anticipate the outcomes of population recovery attempts.